Moderate hypothermia and brain temperature in patients with severe middle cerebral artery infarction - Schwab, Stefan; Schwarz, Stefan; Aschoff, Alfred; Keller, Emanuela; Hacke, Werner (Intracranial pressure and neuromonitoring in brain injury, 1998)
Elevated temperature is known to facilitate neuronal injury after ischemia. After head injury a gradient between temperature and body temperature of up to 3°C degrees higher in the brain has been reported. Hypothermia may limit some of the deleterious metabolic consequences of such increased temperature.